Natural insecticide based on andiroba oil: an alternative for controlling insect pests in açaí groves in lower Tocantins - Menezes, Hellen Claudia Coutinho (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 39 No 76 (2023): Publicação Contínua, 2023)
Açaí is an important socioeconomic product in Brazil, mainly in the Amazon region, especially in the state of Pará. One of the problems that affects its productivity is the increase in pests that attack the açai groves. In this context, the study aims to test the efficiency of natural insecticides produced from Carapa guianensis (andiroba) associated with essential oils and extracts of Rota graveolens L. (rue) and Tagetes patula L. (marines), for the pest insect control present in an açaí plantation in Baixo Tocantins. The extraction of essential oils was carried out through the traditional technique of hydrodistillation for the production of three insecticides. The study was carried out in Nova América, a rural area in the municipality of Oeiras do Pará, in a Euterpe oleracea (açaí) plantation on terra firme, with plants in the young phase with three years and six months of life distributed in eight hectares, the area was delimited in 200 m 2 , divided into four points, three for the application of the natural insecticide and one for the control. A survey of insect pests and application of insecticides were carried out according to the insect population density, with the application being repeated every ten days.